The role of sensation in subjective and objective evaluation of nasal patency - Dipak, S.; Prepageran, N.; Haslinda, S.; Atiya, A.; Raman, R. (2012)
To assess if sensation of nasal mucosa affect the subjective sensation of nasal patency. This is a case control study with 50 patients, using 2% lignocaine as the active drug and normal saline as the placebo (2 groups of 25 patients each). Each subject had 2 ml of solution sprayed into the test nose. These subjects had no prior nasal symptoms, allergy or surgery. They were evaluated subjectively using Likert scale and objectively by acoustic rhinometry before and after lignocaine or normal saline. The patients in both normal saline and lignocaine groups demonstrated no significant change based upon Likert scale. The study also demonstrated the mean cross sectional area 1 (CSA1), mean cross sectional area 2 (CSA2), with mean Volume 1 and mean Volume 2, these results did not vary significantly in both groups with Acoustic Rhinometry. The analysis thus shows that the use of topical anesthetic spray on nasal mucosa produces no objective effect on nasal resistance or subjective sensation of altered nasal patency. Thus the study concludes that, tactile sensation of nasal mucosa does not play a role in the sensation of nasal obstruction.